FIGURE 28. A–D in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 28. A–D, Laleonectes vocans (A. Milne-Edwards, 1878). A, B, Male, cl 11.2 mm, cw 23.6 mm (MZUSP 40174). Note stridulating ridge (arrows) stretching along the lateral walls of the carapace, across the pterygostomial region into the infraorbital margin. C, D, Male, cl 10.2 mm, cw 20 mm (MZUSP 40179). Habitus, dorsal (A, C) and ventral views (B, D). Photographs by A. Pol. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 55, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...